2011
DOI: 10.1080/00222348.2011.579860
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dispersion of Carbon Nanoparticles Modified by Poly(Sodium 4-Styrenesulfonate) and Its Influence on the Properties of Natural Rubber Latex

Abstract: A novel strategy of radical polymerization of sodium 4-styrenesulfonate on the surface of carbon black (CB) in the solid state was developed to prepare hydrophilic carbon nanoparticles (PNASS-CB). A high performance natural rubber latex (NRL)/PNASS-CB composite was produced by the latex compounding technique. Scanning electron microscope shows considerable improvement in the dispersion of PNASS-CB in rubber matrix. The lower degree of filler-filler networks and the stronger filler-rubber interaction of PNASS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, a wide variety of filler modification methods, such as thermomechanical treatment technique, one-step in-situ ball milling, hydrothermal autoclaving and dip and dry method, etc. have been applied to various other fillers, such as carbon black, hydroxyapatite and various other inorganic material as described in the literature [23][24][25][26]. However, as far as we know, studies applying these latter methods to clays have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a wide variety of filler modification methods, such as thermomechanical treatment technique, one-step in-situ ball milling, hydrothermal autoclaving and dip and dry method, etc. have been applied to various other fillers, such as carbon black, hydroxyapatite and various other inorganic material as described in the literature [23][24][25][26]. However, as far as we know, studies applying these latter methods to clays have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Elastomers are generally reinforced by an additional rigid phase for practical use because the intrinsic modulus and strength of rubber is low . Some studies have proposed that the overall properties of a rubber composite can be enhanced even further if better dispersion of particles can be achieved .…”
Section: Introductionmentioning
confidence: 99%